In this page Circumcentre of triangle question10 we are going to see solution of first question.

__Definition__:

The point of concurrency of the perpendicular bisector of the sides of a triangle is called the circumcentre of the triangle.

**Question 10:**

**Find the co ordinates of the circumcentre of a triangle whose**

**vertices are ****(3,1) (0,4) and (-3,1).**

Let A (3,1), B (0,4) and C (-3,1) be the vertices of triangle.

Now we need to find the midpoint of the side AB

Midpoint of AB = [(x₁ + x₂)/2 , (y₁ + y₂)/2]

A (3,1) and B (0,4)

Here x₁ = 3, x₂ = 0 and y₁ = 1,y₂ = 4

= [(3+0)/2,(1+4)/2]

= [3/2,5/2]

= [3/2,5/2]

So the vertices of D is (3/2,5/2)

Slope of AB = [(y₂ - y₁)/(x₂ - x₁)]

= [(4-1)/(0-3)]

= 3/(-3)

= -1

Slope of the perpendicular line through D = -1/slope of AB

= -1/(-1)

= 1

__Equation of the perpendicular line through D:__

(y-y₁) = m (x-x₁)

Here point D is (3/2,5/2)

x₁ = 3/2 ,y₁ = 5/2

(y-5/2) = 1 (x-3/2)

(2y-5)/2 = 1(2x-3)/2

(2y - 5) = (2 x - 3)

2 x - 2 y -3 + 5 = 0

2 x - 2 y + 2 = 0

÷ by 2 => x - y = -1

Equation of the perpendicular line through D is x - y = -1

Now we need to find the midpoint of the side BC

Midpoint of BC = [(x₁ + x₂)/2 , (y₁ + y₂)/2]

B (0,4) and C (-3,1)

Here x₁ = 0, x₂ = -3 and y₁ = 4,y₂ = 1

= [(0 + (-3))/2,(4 + 1)/2]

= [-3/2,5/2]

So the vertices of E is (-3/2,5/2)

Slope of BC = [(y₂ - y₁)/(x₂ - x₁)]

= [(1 - 4)/(-3 - 0)]

= -3/(-3)

= 1

Slope of the perpendicular line through E = -1/slope of BC

= -1/1

= -1

__Equation of the perpendicular line through E:__

(y-y₁) = m (x-x₁)

Here point E is (-3/2,5/2)

x₁ = -3/2,y₁ = 5/2

(y - 5/2) = -1 (x - (-3/2))

(2y - 5)/2 = -1 (2x + 3)/2

2 y - 5 = - 2 x - 3

2 x + 2 y - 5 + 3 = 0

2x + 2 y - 2 = 0

÷ by 2 => x + y = 1

Equation of the perpendicular line through E is x + y = 1

Now we need to solve the equations of perpendicular bisectors D and E

x - y = -1 ---------(1)

x + y = 1 ---------(2)

x - y = -1

x + y = 1

--------------

2 x = 0

x = 0/2

x = 0

Substitute x = 0 in the first equation we get 0 - y = -1

- y = -1

y = 1

So the circumcentre of a triangle ABC is **(0,1) Circumcentre of triangle question10 Circumcentre of triangle question10**

HTML Comment Box is loading comments...

[?]Subscribe To This Site